2019
DOI: 10.3389/fcell.2019.00209
|View full text |Cite
|
Sign up to set email alerts
|

Planar Asymmetries in the C. elegans Embryo Emerge by Differential Retention of aPARs at Cell-Cell Contacts

Abstract: Formation of the anteroposterior and dorsoventral body axis in Caenorhabditis elegans depends on cortical flows and advection of polarity determinants. The role of this patterning mechanism in tissue polarization after formation of cell-cell contacts is not fully understood. Here, we demonstrate that planar asymmetries are established during left-right symmetry breaking: Centripetal cortical flows asymmetrically and differentially advect anterior polarity determinants (aPARs) from contacts to the medial cortex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 70 publications
(127 reference statements)
2
15
0
Order By: Relevance
“…Although the embryo morphology resembles the real one initially, ABpl ingresses inward along the L-R axis instead of migrating in the anterior-ventral direction, leading to a flattened structure in the AP-DV plane with the conserved ABpr-MS contact broken ( S5 and S7A Figs and S5 Movie ). A recent experimental study reported the significantly higher E-cadherin HMR-1 accumulation in ABpl’s anterior contacts than those in the posterior [ 49 ], however, the relatively strong attraction in ABpl-E and ABpl-C contacts (i.e., σ ABpl, E = σ ABpl, C = σ S ) disobeys this observation ( S5 Fig ). Thus, we respectively add the attraction motif onto these contacts to mimic the weak cell-cell adhesion in vivo , namely, σ ABpl, E = σ W and σ ABpl, C = σ W .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the embryo morphology resembles the real one initially, ABpl ingresses inward along the L-R axis instead of migrating in the anterior-ventral direction, leading to a flattened structure in the AP-DV plane with the conserved ABpr-MS contact broken ( S5 and S7A Figs and S5 Movie ). A recent experimental study reported the significantly higher E-cadherin HMR-1 accumulation in ABpl’s anterior contacts than those in the posterior [ 49 ], however, the relatively strong attraction in ABpl-E and ABpl-C contacts (i.e., σ ABpl, E = σ ABpl, C = σ S ) disobeys this observation ( S5 Fig ). Thus, we respectively add the attraction motif onto these contacts to mimic the weak cell-cell adhesion in vivo , namely, σ ABpl, E = σ W and σ ABpl, C = σ W .…”
Section: Resultsmentioning
confidence: 94%
“…Besides, the cell location and cell morphology are highly similar to the ones in vivo , indicating that the model successfully recaptures the physical state of each cell as well as the mechanical interactions between them ( Fig 3A and 3B and S3 and S4 Movies ). The ring-like structure at 7-cell stage, in which ABpl is surrounded by the other 6 cells, was reported to play a pivot role in polarity redistribution and axis establishment ( Fig 3B ) [ 49 ]. Our simulation shows that this geometric pattern is set up by cooperative cell division orientations of ABa, ABp, and EMS, which together make ABpl the embryo’s center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAi was performed by feeding as described earlier ( Dutta et al, 2019 ) using clones from commercially available libraries 1 or prepared from gDNA. All experiments, with exception of pat- 2 and vab-10 in GE24, were performed using L1 staged larva.…”
Section: Methodsmentioning
confidence: 99%
“…Although the initial 8cell structure resembles the real one, ABpl would ingress inward the embryo along L-R axis instead of migrating in anteriorventral direction, resulting in a flattened structure with the conserved ABpr-MS contact broken immediately, which is twodimensional in AP-DV plane eventually(Figures S5 and S7A; Movie S7). A recent work reported the discovery of significantly higher E-cadherin HMR-1 accumulation in ABpl's anterior contacts than those in posterior, and whether this asymmetric enrichment contributes to ABpl's directional migration is yet to be answered(Dutta et al, 2019). Regarding the attraction matrix default, all the three cells anterior to ABpl have strong attraction (i.e., σABal-ABpl = 0.9, σABar-ABpl = 0.9, σABpl-MS = 0.9), however, the contacts with posterior cells E and C are also strong while the one with ABpr is weak (i.e., σABpl-E = 0.9, σABpl-C = 0.9, σ'ABpl-ABpr = 0.2) (Figure S5).…”
mentioning
confidence: 99%